Cause, Magnitude and Contributing Factors for Maternal Death in Selected Hospitals in Snnpr between 2007/2008 and 2009/2010 - Deneke, Yemisrach Shiferaw; Afework, Mesganaw Fantahun; Tessema, Tesfalem Teshome; Misganaw, Chalachew; Taye, Hawult (International Journal of Medical and Health Sciences Research, 2014)
Introduction: Maternal mortality has high public health importance because of its magnitude in Ethiopia. Its reduction is possible. However, factors contributed to maternal mortality not sufficiently identified in Ethiopia. Objective: To identifying cause, magnitude and contributing factors for maternal death in selected hospitals in SNNPR between 2007/2008 and 2009/20010. Method: A retrospective register based study was conducted in SNNPR in purposively selected three hospitals. All maternal deaths recorded during the study period were included. Data were collected by reviewing records using pre-tested checklist. Data collectors were Midwives from health center. Training was given for data collectors and supervisor. Data was entered and cleaned using EPI version 3.5.2. The cleaned data was exported to SPSS version 16, for descriptive statistical analysis. Result: Maternal deaths were 127 & maternal mortality ratio was 1360/100,000 live births. Direct obstetric causes of death accounted for 88%, out of which 31%, 23 % and 15% were obstructed labour, hemorrhage and eclampsia cases, respectively. Low (3.1%) of ANC follows up. Seventy percent of mothers were in labour for 2-3 days at home and 48.4% mothers died on the day of admission. Patients who were potentially in need of blood transfusion, 90%, 84% and 79% of APH, PPH and ruptured uterus cases respectively, died without receiving it. Conclusion: Maternal mortality ratio was high. Obstructed labour was the leading cause of death. Delay in health seeking behavior as patient factor and delay at health facility as provider factor have contributed to maternal death. Based on this finding regional health office was suggested to make the comprehensive emergency obstetric care service accessible to the rural society in which the majority lives and birth preparedness emergency readiness should be enhanced in the community.